2003
DOI: 10.1063/1.1535253
|View full text |Cite
|
Sign up to set email alerts
|

Laser shadowgraph measurements of electromagnetically-driven cylindrical shock-wave implosions in water

Abstract: Experiments performed at the Los Alamos National Laboratory’s Atlas 23-MJ z-pinch capacitor bank facility allows for experimental characterization of electromagnetically-driven cylindrical shock-wave implosions. Time-resolved laser shadowgraphy is used to dynamically image an Atlas-generated liner–target radial shock implosion in water with two-dimensional imaging detail that provides benchmark results for numerical hydrocode validation efforts at Los Alamos. Our laser shadowgraph measurements capture eight se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…[1][2][3][4] Different approaches, for instance, chemical explosion, laser irradiation of a target, Z pinch, and plasma guns, have been used for obtaining ultrahigh pulsed pressure of ϳ10 Mbar with initially stored energy of several megajoules. [1][2][3][4][5][6][7] These experiments, which require expensive and sophisticated equipment, were carried out in a wide timescale range of 10 −3 -10 −14 s. Recently, a converging cylindrical strong shock wave ͑SW͒ which forms as a result of underwater electrical wire array explosion was suggested for generation of ultrahigh pressure at the axis of implosion. 8 Experiments based on initial stored energy of just several kilojoules were carried out with microsecond timescale electrical explosion of a cylindrical wire array applying framing shadow images of the converging SW at different radii and compared with hydrodynamic ͑HD͒ simulations showed that a pressure of ϳ160 kbar can be reached at a radius of 100 m. However, these simulations do require initial SW parameters which cannot be obtained with high accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Different approaches, for instance, chemical explosion, laser irradiation of a target, Z pinch, and plasma guns, have been used for obtaining ultrahigh pulsed pressure of ϳ10 Mbar with initially stored energy of several megajoules. [1][2][3][4][5][6][7] These experiments, which require expensive and sophisticated equipment, were carried out in a wide timescale range of 10 −3 -10 −14 s. Recently, a converging cylindrical strong shock wave ͑SW͒ which forms as a result of underwater electrical wire array explosion was suggested for generation of ultrahigh pressure at the axis of implosion. 8 Experiments based on initial stored energy of just several kilojoules were carried out with microsecond timescale electrical explosion of a cylindrical wire array applying framing shadow images of the converging SW at different radii and compared with hydrodynamic ͑HD͒ simulations showed that a pressure of ϳ160 kbar can be reached at a radius of 100 m. However, these simulations do require initial SW parameters which cannot be obtained with high accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the spherical implosion of an SW allows one to obtain a ðr=r 0 Þ 0:66 larger pressure than does a cylindrical SW implosion for the same initial values of p 0 and r 0 . Indeed, experimental studies of the underwater electrical explosion of a spherical wire array 25,26 and numerical one-dimension HD simulations showed that in the vicinity of the implosion origin (r % 3 lm), one can expect to obtain in water P $ 6 Â 10 12 Pa, T $ 30 eV, and q $ 10 g/cm 3 . In these experiments, also the TOF of the SW to the origin of the implosion was measured.…”
mentioning
confidence: 99%
“…1 eV) state of matter is important for validating existing Equation of State (EOS) databases, conductivity models, some of astrophysical problems, Inertial Confinement Fusion, and various applications. 1 To achieve such a state of matter, different dynamic loading approaches are used, namely, explosive detonation methods, 2 electromagnetically driven cylindrical shock wave (SW) implosion in water, 3 Z-pinch, 4,5 light-gas guns, 6 powerful lasers, [7][8][9] and high-energy intense ion beams. 10 All these dynamic approaches require either special safety measures or pulsed power supplies with MJ range stored energy.…”
mentioning
confidence: 99%
“…We estimated the speeds of the shock fronts for both the diverging and focusing shock waves at 34.6 ns by extracting the shock propagation distances from the image. For an excitation energy of 0.05 mJ, the measured speeds corresponded to 1-D shock pressure 30 of 2.9 ± 1.5 kbar and 1.7 ± 0.5 kbar for the focusing and diverging waves, respectively, as calculated from the following Hugoniot data for water 28 : where u S is the shock speed, c 0 is 1.45 km/s (acoustic velocity in water) and ρ 0 is 0.998 g/cm 3 (density of the undisturbed water at room temperature). The pressures calculated from the density and speed measurements agreed within the respective uncertainties for both laser excitation energies used (see Table 1 ).…”
Section: Discussionmentioning
confidence: 97%